2017
DOI: 10.3390/jof4010002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophobins in Aspergillus fumigatus

Abstract: Resistance of Aspergillus fumigatus conidia to desiccation and their capacity to reach the alveoli are partly due to the presence of a hydrophobic layer composed of a protein from the hydrophobin family, called RodA, which covers the conidial surface. In A. fumigatus there are seven hydrophobins (RodA–RodG) belonging to class I and III. Most of them have never been studied. We constructed single and multiple hydrophobin-deletion mutants until the generation of a hydrophobin-free mutant. The phenotype, immunoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 55 publications
0
84
1
1
Order By: Relevance
“…In A. fumigatus , the conidial cell wall is covered by rodlets, constituted by the class I hydrophobin RodA, and by DHN-melanin. These two layers are responsible for the hydrophobicity of the conidium and its resistance to physical disruption, UV, and desiccation [ 10 ]. Other classes of hydrophobins have been identified in A. fumigatus , but their role remains unknown since they were not able to assembly into rodlets [ 10 ].…”
Section: The Outer Layer Of the Cell Wall Is A Protective Barriermentioning
confidence: 99%
“…In A. fumigatus , the conidial cell wall is covered by rodlets, constituted by the class I hydrophobin RodA, and by DHN-melanin. These two layers are responsible for the hydrophobicity of the conidium and its resistance to physical disruption, UV, and desiccation [ 10 ]. Other classes of hydrophobins have been identified in A. fumigatus , but their role remains unknown since they were not able to assembly into rodlets [ 10 ].…”
Section: The Outer Layer Of the Cell Wall Is A Protective Barriermentioning
confidence: 99%
“…RodA exhibited the highest levels of normalized abundance throughout germination; ranging from 16.8% to 7.7% of the normalized peptide spectrum matches (PSMs) per length and consistent with previous study. 26,32 The majority of conidia underwent germination in our assays; however, a small fraction of conidia failed to germinate, which likely contributed to the abundance of RodA at later time points. In agreement, localization studies with a polyclonal RodA antibody revealed the presence of RodA on the surface of conidia, in biofilm cell walls, and in phialides during sporulation.…”
Section: Resultsmentioning
confidence: 94%
“…[29][30][31] Despite this key function, RodA is not required for virulence in a mammalian infection model. 30,32 Aside from RodA, the functions of few other A. fumigatus surface-exposed proteins are known. In many cases, these proteins seem to play important, but enigmatic roles in fungal biology, as is the case with the recently described CcpA protein, which serves as a conidial protein important for virulence in a mouse infection model.…”
mentioning
confidence: 99%
“…The human PTX3 protein directly recognizes A. fumigatus via its N-terminal domain [25]; however, this is restricted to resting, swollen, and germinating conidia, with little or no interaction with fungal hyphae [24]. Based on competition experiments, GM has been proposed as ligand of PTX3 [24]; however, this polysaccharide is enveloped in the layer of RodA and DHN melanin of dormant conidia [6,43] (that are bound by PTX3) and is abundant and exposed in the hyphal wall [69] (that is poorly or not recognized by PTX3), and no direct interaction of PTX3 with purified GM has been reported so far, which suggests that other cell wall components are recognized by this long pentraxin. Indirect binding of PTX3 to A. fumigatus conidia has also been reported.…”
Section: Ptx3 In the Immune Response To Aspergillus Fumigatus And Itsmentioning
confidence: 99%
“…The metabolically inactive and asexual airborne spores (known as dormant or resting conidia) are encased in a robust cell wall mostly made of complex polysaccharides [i.e., aand b-glucans, chitin, galactomannan (GM), and galactosaminogalactan (GAG)] in addition to lipids, proteins, and melanin pigments [i.e., dihydroxynaphthalene (DHN) melanin] [4]. Small in size (i.e., 2-3 µm across) and enveloped in a layer of hydrophobic rodlet-like proteins (i.e., RodA, that imparts air buoyancy and, most importantly, immunological inertness [5,6]), conidia of A. fumigatus are naturally fit for air/water interfaces, which favors their penetration into the lower respiratory tracts (i.e., lung alveoli) of the mammalian host [7]. Up to hundreds of conidia are inhaled daily by humans; nonetheless, this incessant infectious challenge rarely involves lung colonization and disease in immunocompetent individuals.…”
mentioning
confidence: 99%